Morphological characterization and taxonomic key for tadpoles of Brazilian Cerrado - Santos, Danusy Lopes [UNESP] (2023)
Currently, amphibians are recognized as the most threatened vertebrate group worldwide. In this context, studies that offer tools for amphibian conservation are strategic to reduce the threats to this group. The absence of detailed descriptions and morphological variation of the anuran larval stage and the lack of identification tools increase the difficulty of anuran larval stage identification by non-specialists. Here we present the morphological characterization of tadpoles of 49 anuran species that occur in the Cerrado biome and transitional areas. Also, we compared our characterization with available descriptions of the tadpole and provided comments about the morphological variation found in our samples. Finally, we produced a taxonomic key as a tool for species identification using the anuran larval stage.